PEMBELAJARAN KOOPERATIF TIPE STRUCTURE NUMBERED HEADS PADA MATA PELAJARAN GEOGRAFI - Miftah Hidayat (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
Abstract The purpose of this research is to: (1) increase the learning motivation of learners by using Structure Numbered Heads learning method, and (2) to describe the improvement of learning motivation of learners through Structure Numbered Heads learning method. The method used is Classroom Action Research which refers to the model developed by Kemmis and Taggart, this study was conducted in two cycles. One cycle is done as much as two actions. Thus the entire Classroom Action Research was conducted in 4 actions. Data collection techniques are done through observation and documentation. The result of the research shows that learning done with cooperative learning model type Structure Numbered Heads can improve learners motivation. The first action shows the